Fast investigative lung cancer pathway and endobronchial ultrasound procedure supported by rapid on‐site evaluation. Issue 9 (9th July 2022) - Khan, Kashif Ali; Narine, Nadira; Bailey, Simon; Shelton, David; Rana, Durgesh
Abstract: Introduction: EBUS is a well‐established tool for diagnosis and staging of lung cancer in a fast track investigative pathway. However, impact of ROSE in conjunction with EBUS on reduction of time to treatment decision (TTD) for cancer patients is less well known. Aims: Our aim was to determine TTD which was defined as the number of working days from EBUS procedure to the discussion at sector lung multidisciplinary team meeting (MDT). Moreover, concordance of ROSE with final diagnosis was evaluated. Methods: A retrospective analysis was performed of a prospective data collection in a busy teaching hospital over a four months study period (September to December 2018). Results: Data from 112 patients was analyzed. There were 61 (54%) males. Mean age was of 70 years (range 43–91). WHO performance status was 0 in 20 (23%), 1 in 57 (51%), 2 in 22 (20%) and 3 in 7 (6%) patients. In total 522 needle passes were performed from 242 sampling sites. Average working days to discuss at MDT after optimal EBUS sampling was 2.087 (range 0–13 working days). ROSE concordance with final cytological diagnosis was 98.4%. The number of needle passes per site for adequate sample and diagnosis in malignant (4.929) vs non‐malignant (2.776) involvement was significantly different ( p value <0.0001). There was 100% sample adequacy for preliminary diagnosis, immunohistochemistry and predictive molecular testing. Conclusion: ROSE supported fast‐investigative pathway by reducing the time to treatment decision (TTD) making at MDT. High concordance with final cytological diagnosis makes it an effective tool to inform meaningful decision making.